The Use of Paired Reading Technique in Improving Student’s Reading Comprehension Skill at SMA Negeri 2 Tondano - Loho, Danny K. P.; Oroh, Elisabeth Z.; Rombepajung, Paula A. (JoTELL : Journal of Teaching English, Linguistics, and Literature, 2024)
Reading is a skill which involves the students prior knowledge of the learned language and the students understanding on written forms. Paired Reading is a Technique for improving reading fluency and comprehension in which student is paired and takes turns being the tutor and the tutee. Students sit side-by-side while one reads and the other follows along, assisted by the teacher when necessary. The narrative is a text that relates a series of logically or chronologically related events caused by some factors. The essential key to comprehending narrative text is the plot, character, and event. This type of research is quantitative, Which will use a the Pre-experimental approach and a one-group pre-test design. The instrument that researchers will use is reading narrative text with 25 multiple choice. The sample that researcher will use is class XI, totaling 20 students. the results of calculations or analyses from the SPSS application, which shows that the average score resulting from the pre-test is 55.3. This figure is low in terms of learning outcomes. By carrying out treatment on the students, from the results of the treatment, the average score for the post-test was obtained, namely 85.75. With this number, we can see that there has been an improvement in this research. For this reason, with the two average values, it can be concluded, or we can say that the treatment was successful